THE EXPRESSION OF HIDDEN MEANING THROUGH IRONY AND ITS MANIFESTATIONS IN TWO LANGUAGES - Abduqodirova Madina Abduqayum qizi (PEDAGOGS, 2025)
Annotation. This article analyzes the characteristics of expressing hidden meaning through irony. It explores how irony manifests across different cultures and languages, focusing on its linguistic and pragmatic features. The study compares the use of irony in English and Russian, highlighting both similarities and differences in their use of implicit meaning. Special attention is also given to the role of irony in translation.